Upaya meningkatkan sikap ilmiah dan hasil belajar kimia melalui penerapan model pembelajaran inkuiri - I Ketut Mardika (Indonesian Journal of Educational Development, 2020)
The inquiry learning model is implemented to improve scientific attitudes and chemistry learning achievements of SMA Negeri 1 Marga students. The research objective is to investigate the inquiry learning model that can improve scientific attitudes and chemistry learning achievement. The research subjects were students of class X MIPA2 of SMA Negeri 1 Marga in 1 st semester of the 2019/2020 academic year which is consisting of 39 people. The object of research is scientificattitude and chemistry learning achievement. The scientific attitude data was collected using an observation sheet, while the chemistry learning achievement was collected using a learning achievement test. The data analysis technique used is descriptive qualitative. To evaluate the success of the study, the following criteria were established: (1) the scientific attitude of students at least good category; (2) minimum chemistry learning achievement score of KKM 68 and (3) masterylearning at least 85%. The average chemistry score of students before the study was 65.18 and mastery learning 79.69%. After conducting an action research the results achieved in cycle I: (1) the scientific attitude of students in the category is quite good; (2) the average chemistry learning achievement score of 69.75 and (3) mastery learning 82.05%. Considering the success criteria have not been achieved, then it is continued with the implementation of research in the second cycle with the following results: (1) students' scientific attitudes are in good category; (2) average chemistry learning achievement score of 71.89 and (3) mastery learning 89.74%. Model pembelajaran inkuiri diimplementasikan untuk meningkatkan sikap ilmiah dan hasil belajar kimia peserta didik SMA Negeri 1 Marga. Tujuan penelitian adalah untuk mengetahui sejauh mana model pembelajaran inkuiri dapat meningkatkan sikap ilmiah dan hasil belajar kimia. Subjek penelitian adalah peserta didik kelas X MIPA2 SMA Negeri 1 Marga semester 1 (satu) tahun pelajaran 2019/2020 yang berjumlah 39 orang. Objek penelitian adalah sikap ilmiah dan hasil belajar kimia. Data sikap ilmiah dikumpulkan menggunakan lembar observasi, sedangkan hasil belajar kimia dikumpulkan menggunakan tes hasil belajar. Teknikanalisis data yang digunakan adalah deskriptif kualitatif. Untuk melihat keberhasilanpenelitian, ditetapkan kriteria sebagai berikut: (1) sikap ilmiah peserta didik minimaldalam kategori baik; (2) nilai rata-rata hasil belajar kimia minimal sebesar KKM 68dan (3) ketuntasan belajar secara klasikal minimal 85%. Nilai rata-rata kimia peserta didik sebelum penelitian dilakukan adalah 65,18 dan ketuntasan belajar klasikal 79,69%. Setelah dilakukan penelitian tindakan hasil yang dicapai pada siklus I: (1) sikap ilmiah peserta didik dalam kategori cukup baik; (2) nilai rata-rata hasil belajar kimia 69,75 dan (3) ketuntasan belajar secara klasikal 82,05%. Mengingat kriteria keberhasilan belum tercapai, maka dilanjutkan dengan pelaksanaan penelitian di siklus II dengan hasil sebagai berikut: (1) sikap ilmiah peserta didik dalam kategori baik; (2) nilai rata-rata hasil belajar kimia 71,89 dan (3)ketuntasan belajar secara klasikal 89,74%.